Occluded left main stem coronary artery. Report of five patients and review of published reports. Issue 3 (March 1983) - Ward, D E; Valantine, H; Hui, W
Abstract : Five patients aged 24 to 62 years presenting with a long history of angina were found to have complete occlusion of the left main coronary artery. In one patient the right coronary artery was also completely blocked. All patients had a dominant right coronary artery which was significantly diseased in only one patient. Ventricular function was severely impaired in only one patient. These patients illustrate the importance of collateral information in this condition. Coronary bypass grafting was performed in three patients who are now symptomatic at follow-up between nine and 17 months.